KINERJA PEGAWAI DIPENGARUHI OLEH DISIPLIN KERJA MELALUI MOTIVASI KERJA PUSAT PENGEMBANGAN SUMBER DAYA MANUSIA KETENAGAKERJAAN - Andriani Syariy Suhendra; Eddy Sanusi Silitonga (Jurnal Ekonomi dan Industri, 2025)
This research was conducted to determine whether employee performance at the Human Resources Development Center for Employment is influenced by work discipline through work motivation. This study used a quantitative approach. The population employees of the Center for Human Resources Development and Employment. The data analysis method used path analysis. The research results show that: 1) Work discipline has a positive and significant effect on employee performance; 2) Work motivation has a positive and significant effect on employee performance; 3) Work discipline has a positive and significant effect on work motivation; and 4) work discipline influences employee performance through work motivation at the Center for Human Resources Development and Employment.